Effectiveness of Social Adjustment Training Program on Perceived Competence, Academic Enthusiasm and Sense of School Belonging in Boy Students - Hasan Shafiei; Mohammad Saleh Rostami (مطالعات روانشناسی تربیتی, 2023)
The aim of this study was to investigate the effectiveness of social adjustment training program on perceived competence, academic enthusiasm and sense of school belonging in boy students. The research method was semi-experimental with pretest-posttest design with control group. The statistical population consisted of all boys' secondary high school students in the academic year of 2020-2021in the city of Saqqez (N = 2300) and 30 people were selected through the convenience sampling method and randomly divided into experimental (n=15) and control (n=15) groups. For gathering data the questionnaires of perceived competence (Harter, 1982) academic enthusiasm (Fredericks, Blumenfield and Paris, 2004) and sense of school belonging (Barry, Batey and Watt, 2005) were used. The students of the experimental group underwen 10 sessions of 90 minutes for 5 consecutive weeks (2 sessions per week) of social adjustment training program (Najari, Jaidi, Moradi and Karimi, 2017) and the control group did not receive any intervention. data were analyzed using multivariate analysis of covariance. The results of this study showed that social adjustment training program had a significant effect on increasing the perceived competence (p=0.048), academic enthusiasm (p=0.049) and the sense of school belonging (p=0.040) in boy students. overall, the results showed the effectiveness of the social adjustment training program as an effective method for increasing perceived competence, academic enthusiasm and the sense of school belonging in boy students. It is suggested that this program be used by custodians of education and educational institutions to design preventive educational programs and improve educational achievements.